Incorporating optimisation in strategic conflict resolution service in U-space - Tang, Yiwen; Xu, Yan; Inalhan, Gokhan (SESAR, 2021)
This study presents an approach to incorporate optimisation in the strategic conflict resolution service in U-space. A conventional approach in line with the First-Come, First-Served (FCFS) rule is introduced, following the generation of two types of flight plans (i.e., linear and area operations) with uncertainty buffers further taken into account. This approach is based on iteratively checking the availability of the shared airspace volumes. Next, an optimisation model is formulated, using the same concept of common airspace representation, aiming at minimising the overall delay subject to operational constraints including a time-based separation minima. Some potential implementations are also envisioned for the optimisation model under plausible operational scenarios. Finally, simulation experiments are performed where four different case studies are designed, including FCFS and optimisation, as well as a hybrid use of both depending on the flight plans’ submission time. Results suggest that, compared to FCFS, a notable delay reduction can be achieved with the optimisation approach incorporated, which is due to the FCFS prioritisation scheme that is often not efficient.
Keywords: UTM; U-space; strategic conflict resolution; UTM; U-space; strategic conflict resolution; first-come, first-served (FCFS); optimisation; first-come, first-served (FCFS); optimisation